2015
DOI: 10.1016/j.jphs.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Depositing α-mangostin nanoparticles to sebaceous gland area for acne treatment

Abstract: Although entrapment of nanoparticles of appropriate sizes at hair follicles has been clarified, there is no report on specific clinical application of this finding. Since sebaceous gland is associated with hair follicle, we hypothesize that effective acne vulgaris treatment/prevention can be achieved by depositing anti-acne agent in nanoparticle form at the hair follicles. Challenge of this strategy, however, lies at the finding of effective anti-acne particles with minimal skin irritation. Here using cellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 21 publications
1
35
0
3
Order By: Relevance
“…Impressively, the anti-acne activity of the nanoparticle system significantly decreased the acne severity index (ASI) value and inflammatory lesions (P < 0.05) compared to control. 77 Another study developed a nanoparticle system based on chitosan/alginate and genipin (GP) as a crosslinker prepared using the ionotropic gelation method. The system aimed to achieve a controlled release system and increase the antitumor activity of α-mangostin.…”
Section: Polymeric Nanoparticles Of α-Mangostinmentioning
confidence: 99%
See 1 more Smart Citation
“…Impressively, the anti-acne activity of the nanoparticle system significantly decreased the acne severity index (ASI) value and inflammatory lesions (P < 0.05) compared to control. 77 Another study developed a nanoparticle system based on chitosan/alginate and genipin (GP) as a crosslinker prepared using the ionotropic gelation method. The system aimed to achieve a controlled release system and increase the antitumor activity of α-mangostin.…”
Section: Polymeric Nanoparticles Of α-Mangostinmentioning
confidence: 99%
“…The nanomicelle uptake was mediated by endocytosis, a finding that indicated intracellular delivery of α-mangostin that could be associated with potential cytotoxicity (IC 50 of 8.9 ± 0.2 μg/mL). 82 Chitosan, PLGA Colloidal extraction solvent evaporation [75] PEG, PLA Emulsion/solvent evaporation techniques [76] PLGA Double emulsion solvent evaporation method [42] EC-MC Spray drying [77] Chitosan, alginate and genipin Ionotropic gelation method [78] β-cyclodextrin Inclusion complex technique [79] β-cyclodextrin-chitosan Inclusion complex [80] β-cyclodextrin Inclusion complex [81] Nanomicelles PVP Solvent evaporation method [82] MPEG and PLA Single-step self-assembly method [83] MPEG and PCL Self-assembly method [84] Liposome nanoparticles Transferrin Thin film hydration [85] Soya lecithin Phase separation coacervation method [86] Cholesterol, Tween 60 and ethanol Film hydration method [87] Solid lipid nanoparticles Lavender essential oil and cetyl palmitate Hot and high-pressure homogenisation techniques [88] PLGA and CD44 thioaptamer Nanoprecipitation combined with self-assembly [89] Nanofibres Thiolated chitosan Electrospinning [90] PVP Electrospinning [91] Metal nanoparticles Ag (silver) Chemical reaction by using silver nitrate (AgNO3) [92] Gold, PEI, cyclodextrin and tanshinone Chemical reaction using polyethyleneimine (PEI) [93] Emulsion nanoparticle Captex 200 P, Tween 80, carbopol 90 and silica Solid self-emulsification [94] Oleic acid, isopropyl myristate, Cremophor EL, Tween 80, carboxymethylcellulose sodium Self-microemulsion [31] In another study, α-mangostin nanomicelles with methoxypoly(ethylene glycol)-poly(lactide) (MPEG-PLA) were developed by a single-step self-assembly method for malignant glioma. In vitro and in vivo assays showed that the α-mangostin/MPEG-PLA nanoparticles inhibited cell growth and induced apoptosis-with cleaved caspase expression, DNA fragmentation, downregulation of antiapoptotic molecules and up-regulation of apoptotic molecules.…”
Section: Nanomicellesmentioning
confidence: 99%
“…Based on the time‐kill assay results, topical products should be formulated with a delivery vehicle that may increase the time of skin adhesion, such as a gel or cream, in order to have a sustained release over a period of time. A study in humans used cellulose‐based nanoparticles as a nano‐reservoir and α‐mangostin as an anti‐acne agent; the four week, randomized, double‐blind, placebo‐controlled study in 10 acne patients indicated a significant improvement in their acne vulgaris when the topical product was used twice a day . The mangostin nanoparticle was prepared in a gel base that was composed of water, xanthan gum, propylene glycol, glycerin, allantoin and preservatives …”
Section: Discussionmentioning
confidence: 99%
“…The loss of β cell number and function is associated with type I and II diabetes, and increasing the population has been hypothesized as a cure [69]. Although topically applied α mangostin clinically improved acne severity and inhibited growth of both Staphylococcus epidermidis and P. acnes in vitro [23,70,71], orally-administered extracts have not been tested as an acne treatment. The various activities suggest that Garcinia fruits may be worth studying for their effects on acne with oral supplementation.…”
Section: Edible Plants and Acnementioning
confidence: 99%